Analisis Pemasaran Ternak Babi Hidup di Pasar Gokat - Katarina Yunita Riti; Irmina Kewu Dunga; Osna Leni Malo; Julianto Malo; Samuel Dapa Loka; Darius Ndara Milla (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This study aims to analyze the marketing system of live pigs at Gokat Market, which is one of the centers of pig trade in Indonesia. This analysis includes marketing channels, factors that influence prices, and the relationship between demand and supply of live pigs. The method used in this study is descriptive with a qualitative approach, involving interviews with farmers, traders, and other related parties at Gokat Market. The results of the study indicate that marketing of live pigs involves several channels, ranging from small farmers, collectors, to large traders who sell to end consumers or slaughterhouses. The price of pigs is influenced by the quality of livestock, market demand, and economic conditions, as well as fluctuations in the price of animal feed. The demand for pork is highly dependent on seasonal factors and celebrations, while supply is influenced by the number of farmers and the health conditions of livestock. Regulations also affect market stability and livestock prices. This study concludes that marketing of live pigs at Gokat Market has complex dynamics, where various external and internal factors affect the smooth distribution and selling price of live pigs. Cooperation is needed between farmers, traders, and the government to create a more efficient and sustainable marketing system.